A rational approach to radiodiagnostic investigations : report of a WHO Scientific Group on the Indications for and Limitations of Major X-Ray Diagnostic Investigations, meeting held in Geneva from 9 to 15 November 1982 - World Health Organization; World Health Organization (WHO) Scientific Group (Geneva : World Health Organization, 1983)
Provides clear advice on specific indications and procedures of diagnostic radiology intended to help radiologists and the medical profession reduce the number of routinely performed, clinically useless tests. Now recognized as a landmark, the book focused attention on the inherent limitations of certain examinations as well as on the high costs, risks to patients, and increased population exposure to radiation that result from the excessive use of radiodiagnostic examinations. Advice is presented for investigations of the chest, skeleton, and abdomen. Each of the major tests is assessed in terms of indications and limitations. For the chest, guidance covers routine examinations, radiography in 10 groups of patients, and mammography. Different techniques and projections are also critically assessed. The section on skeletal examinations covers investigations of the skull in trauma and non-trauma cases, spine, limbs, pelvimetry, and bone surveys. The final section offers advice on abdominal surveys, barium examination, oral cholecystography, intravenous urography, renal angiography, and obstetric radiology.
Keywords: A rational approach to radiodiagnostic investigations